2020
DOI: 10.18203/issn.2455-4510.intjresorthop20201017
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome evaluation of distal humerus fracture fixation

Abstract: <p class="abstract"><strong>Background:</strong> Distal humerus fracture are complex, difficult to reduce and fix, cumbersome post-operative mobilization, and yet functional outcome is doubtful. Though various treatment modalities available for past many decades ranging from conservative management, K wire fixation to plate and screws, but still treatment remains difficult. The objective of the study was to assess functional outcome of operative fixation of distal humerus with locking plate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The goals of surgical treatment are to restore articular congruity and bone alignment whilst providing rigid, stable fixation that enables early active motion [7 , 8]. Previous biomechanical studies on internal fixation methods for distal humerus fractures have indicated that double-plate fixation provides adequate stability [10,11]. The standard method used by most surgeons is the application of 2 plates perpendicular to each other, with 1 on the medial supracondylar ridge and the other placed posterolaterally [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The goals of surgical treatment are to restore articular congruity and bone alignment whilst providing rigid, stable fixation that enables early active motion [7 , 8]. Previous biomechanical studies on internal fixation methods for distal humerus fractures have indicated that double-plate fixation provides adequate stability [10,11]. The standard method used by most surgeons is the application of 2 plates perpendicular to each other, with 1 on the medial supracondylar ridge and the other placed posterolaterally [13,14].…”
Section: Introductionmentioning
confidence: 99%